Sentido de vida y generatividad en profesores rurales chilenos - Sandoval-Obando, Eduardo (Cauriensia, 2023)
Objective: To interpret from a narrative perspective those strategies that favor the emergence of potentially generative behaviors on the part of teachers, contributing to the systematization of new ways of understanding the professional work of Chilean rural teachers. Method: a qualitative interpretive approach is adopted, following a descriptive, exploratory and transversal design. The sample is of an intentional nature, made up of 12 educators who have 33 years of experience in rural schools present in the Metropolitan, La Araucanía and Los Ríos Regions (Chile). For the interpretation of the data, content analysis is used, following the logic of the Grounded Theory and the In-Depth Interviews from the generative narrative perspective. Results: The strategies that favor the deployment of generative behaviors are the sense of life and spirituality, expressed in autonomy, flexibility and a high pedagogical involvement in their professional work, as well as a high sense of self-efficacy in their educational task. Finally, the teaching staff reveals a generative sense of life in which challenging personal goals and projects converge that contribute to the development of the communities in which they operate daily, configuring an educational legacy that transcends time.